Mass Violence and the Self : From the French Wars of Religion to the Paris Commune - Brown, Howard G. (Book collections on Project MUSE., 2018)
"Examines the visual and textual media depicting personal suffering caused by incidents of mass violence in France from 1560 to 1880 that helped to provoke repeated collective traumas, which in turn forged new social identities and fostered the psychological processes of the modern self"--